Cardiopulmonary exercise testing for personalized job reintegration after acute cardiovascular attacks: a pilot cross-sectional study - Tanzi, Chiara; Moderato, Luca; Magnani, Francesco; Fallani, Gaia; Marozza, Giovanni; Pizzarotti, Silvia; Zoppi, Bruno; Lazzeroni, Davide; Brambilla, Lorenzo; Coruzzi, Paolo (La Medicina del Lavoro, 2020)
Background: Cardiovascular diseases (CVD), particularly the ischemic heart disease, are a growing public health issue. In addition, the return to work after an acute cardiovascular attack represents a complex challenge. Objectives: To evaluate utility and safety of cardiopulmonary exercise testing (CPET), particularly performed “on site”, to promote a return to work in line with the residual working capacity. Methods: Fifty-nine workers affected by a major cardiovascular event, aged 18-63 years, have been enrolled between 2015 and 2018. All the patients underwent a cardiopulmonary exercise testing (CPET) in outpatient clinic. Eleven workers also underwent the “on site” CPET, recorded during their working activities. Results: Outpatient clinic CPET outcomes (i.e. normal, mild impairment or moderate/severe impairment of cardiopulmonary function) were associated with the subjective perception of workers’ health status after returning to work. The “on site” CPET was found to be safe and reliable to promote a personalized return to work of patients. In 7 out of 11 patients, the values of O2 consumption (VO2) during the working activity were higher than 40% of VO2 max as obtained from laboratory CPET. Conclusions: This study provides evidence for safety and usefulness of “on site” CPET for a personalized statement of fitness for work. This may facilitate the job retention of patients characterized by a high risk of unnecessary job loss. The use of CPET represents a first step of energy expenditure evaluation associated with specific working tasks.